2019
DOI: 10.1016/j.canlet.2019.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor isoform A favors tumor progression in human hepatocellular carcinoma by increasing stem/progenitor cell features

Abstract: Hepatocellular carcinoma (HCC) is one of the most common and deadly neoplasms. Insulin receptor (IR) exists in two isoforms, IR-A and IR-B, the latter being predominantly expressed in normal adult hepatocytes while IR-A is overexpressed in HCC to the detriment of IR-B. This study evaluated the biological functions associated with IR-A overexpression in HCC in relation to expression of its ligand IGF-II. The value of INSRA:INSRB ratio which was increased in ˜7 0% of 85 HCC was associated with stem/progenitor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Even though the concept that an increase in RTK ligands acting in a paracrine or autocrine manner is responsible for native and/or acquired drug resistance in not new [165], no study so far has directly addressed the role of autocrine IGF-II through its RTKs (IR A and IGFIR) under these circumstances. Altogether, the evidence that IGF-II is also used by cancer stem cells, besides being commonly expressed in solid cancers [166][167][168][169], supported by the findings already obtained using genetic, molecular, and cellular approaches, suggests further new hypotheses. In particular, the observation that the presence of autocrine IGF-II loops is associated with overtly malignant cancer cell lines [14,45,94,[170][171][172][173] and that IGF-II over-expression overlaps with those cancer types currently poorly responsive to immune checkpoint therapy (such as malignant mesothelioma [174][175][176], glioblastoma [177,178], and pancreatic carcinoma [179,180]) along with certain BRAF-inhibitor-treated recurring cancers [181,182] suggest that the autocrine IGF-II/IR A axis role under these circumstances should be investigated and its targeting potential experimentally vetted.…”
Section: Targeting the Autocrine Igfii/ir A Loop In Cancer: A Furthermentioning
confidence: 58%
“…Even though the concept that an increase in RTK ligands acting in a paracrine or autocrine manner is responsible for native and/or acquired drug resistance in not new [165], no study so far has directly addressed the role of autocrine IGF-II through its RTKs (IR A and IGFIR) under these circumstances. Altogether, the evidence that IGF-II is also used by cancer stem cells, besides being commonly expressed in solid cancers [166][167][168][169], supported by the findings already obtained using genetic, molecular, and cellular approaches, suggests further new hypotheses. In particular, the observation that the presence of autocrine IGF-II loops is associated with overtly malignant cancer cell lines [14,45,94,[170][171][172][173] and that IGF-II over-expression overlaps with those cancer types currently poorly responsive to immune checkpoint therapy (such as malignant mesothelioma [174][175][176], glioblastoma [177,178], and pancreatic carcinoma [179,180]) along with certain BRAF-inhibitor-treated recurring cancers [181,182] suggest that the autocrine IGF-II/IR A axis role under these circumstances should be investigated and its targeting potential experimentally vetted.…”
Section: Targeting the Autocrine Igfii/ir A Loop In Cancer: A Furthermentioning
confidence: 58%
“… 18 High levels of IR-A are implicated in tumorigenesis and are found in various cancers including breast, endometrial, colon and hepatocellular cancer. 20 22 IR-A also shows an increased affinity for IGFs compared with IR-B. 23 IGF-1 and IGF-2 are small peptides synthesised in the liver in response to growth hormone.…”
Section: Obesity and Dysregulated Insulin Signallingmentioning
confidence: 99%
“…Benabou et al showed that overexpression of the Huh7-insulin receptor isoform A (IRA) caused an increase in the expression levels of IGF-2 and stemness markers CK19, CD133, CD44, EpCAM, and PROM1. Knocking down IGF-2 expression by siRNA repressed phosphorylation of IR [172]. Downstream of growth signaling (IGF-1R, EGFR), long noncoding RNA (lncRNA) H19 regulates cancer stemness and EMT markers in HepG2 and Hep3B2.1-7 cell lines.…”
Section: Igf/igf-1r Signaling Induces Expressions Of Stemness-relatedmentioning
confidence: 99%